2012
DOI: 10.1371/journal.pone.0037072
|View full text |Cite
|
Sign up to set email alerts
|

Improving Oral Hygiene Skills by Computer-Based Training: A Randomized Controlled Comparison of the Modified Bass and the Fones Techniques

Abstract: BackgroundGingivitis and other plaque-associated diseases have a high prevalence in western communities even though the majority of adults report daily oral hygiene. This indicates a lack of oral hygiene skills. Currently, there is no clear evidence as to which brushing technique would bring about the best oral hygiene skills. While the modified Bass technique is often recommended by dentists and in textbooks, the Fones technique is often recommended in patient brochures. Still, standardized comparisons of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
57
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 22 publications
15
57
2
Order By: Relevance
“…But our result is contrast with Hernacke D et al, who found Fones method superior in removing plaque as compared to modified Bass technique. 18 Our results are in accordance with Robinson, who found Bass technique as most effective in the plaque removal.…”
supporting
confidence: 92%
“…But our result is contrast with Hernacke D et al, who found Fones method superior in removing plaque as compared to modified Bass technique. 18 Our results are in accordance with Robinson, who found Bass technique as most effective in the plaque removal.…”
supporting
confidence: 92%
“…, Hoffmann , Harnacke et al. , b), oral cleanliness was far from perfect after participants had been asked to perform oral hygiene to the best of their abilities. Thus, at the end of the long years of prophylactic efforts sustained by public authorities, these young adults appear to be unable to cleanse the majority of their gingival margins of adjacent plaque.…”
Section: Discussionmentioning
confidence: 99%
“…, Harnacke et al. ,b) was assessed immediately after participants had been asked to clean their teeth to the best of their abilities (toothbrush, tooth paste and dental floss were provided). The MPI monitors stained (Mira‐2‐tone ® ‐solution; Hager & Werken, GMBH & Co, Duisburg, Germany) plaque deposits next to the gingival margin as present or absent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] As well, sensor-based toothbrushes, another direct method of evaluation, are available and increasingly provide intricate details of TB. Notably, the newly emerging smart toothbrushes [34–38] such as those by Oral-B™ (http://oralb.com/en-us/product-collections/bluetooth) which uses sensors and the Prophix toothbrush (https://www.getprophix.com) which uses cameras and a view screen are compatible with and could enable new advantages for our approach.…”
Section: Discussionmentioning
confidence: 99%